2005
DOI: 10.1097/01.ccm.0000187010.14426.cc
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid antagonist AM 281 reduces mortality rate and neurologic dysfunction after cecal ligation and puncture in rats

Abstract: Administration of AM 281 prevented the hemodynamic changes and development of neurologic dysfunction occurring in association with septic shock, and could decrease the mortality rate in experimentally induced septic shock in rats. Although further studies are necessary to determine whether endogenous cannabinoids cause septic encephalopathy in rats directly or via their effects on systemic hemodynamics, the beneficial effects of AM 281 on these rats might have significant therapeutic implications in cases of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It has been reported that the cannabinoid antagonist AM281 reduced the mortality rate and neurologic dysfunction after CLP in rats (19). This antagonist has a much higher affinity for CB1R as compared with CB2R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the cannabinoid antagonist AM281 reduced the mortality rate and neurologic dysfunction after CLP in rats (19). This antagonist has a much higher affinity for CB1R as compared with CB2R.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo pharmacology studies with this compound have been shown to reduce mortality in rats following cecal ligation and puncture (CLP) (19). Additionally, AM281 treatment during the rat peritonitis model prevented neurological dysfunction as well as changes in systemic hemodynamics (19, 20). Finally, AM281 administration attenuated serum TNF-α and IL-1β levels up to 3 h following an LPS injection (21).…”
mentioning
confidence: 99%
“…In addition to their well‐known immunological and neurobehavioral actions, CBs and their endogenous and synthetic analogues exert complex cardiodepressive and vasodilatory effects, which have been implicated in the mechanism of hypotension associated with haemorrhagic ( Wagner et al , 1997 ; Cainazzo et al , 2002 ), endotoxic ( Varga et al , 1998 ; Liu et al , 2003 , 2006 ; Batkai et al , 2004a ; Kadoi and Goto, 2006 ), septic ( Kadoi et al , 2005 ), and cardiogenic shock ( Wagner et al , 2001 , 2003 ), advanced liver cirrhosis ( Batkai et al , 2001 ; Ros et al , 2002 ), cirrhotic cardiomyopathy ( Gaskari et al , 2005 ; Pacher et al , 2005c ; Moezi et al , 2006 ; Yang et al , 2007 ; Batkai et al , 2007a ), doxorubicin‐induced heart failure ( Mukhopadhyay et al , 2007 ) and the shock associated with necrotizing pancreatitis ( Matsuda et al , 2005 ). Importantly, these cardiovascular depressive effects could be prevented or reversed by pretreatment with CB 1 antagonists, and are subjects of numerous comprehensive recent overviews ( Randall et al , 2002 ; Hiley and Ford, 2004 ; Lamontagne et al , 2006 ; Lepicier et al , 2006 ; Mallat et al , 2007 ; Mendizabal and Adler‐Graschinsky, 2007 ; Pacher et al , 2005a , 2005b , 2006a ).…”
Section: Circulatory Shock (Full Organ/body Ischaemia And/or I/r)mentioning
confidence: 99%
“…While in another study, CB2R seems like a strong destroyer in the same sepsis model [15]. Cannabinoid antagonist AM 281 was reported to reduce mortality rate after CLP in rats [16], while very recently, Lehmann and his colleagues found that CB2R activation reduced intestinal leukocyte recruitment and inflammation in rat acute sepsis models [17]. These controversial results leave this issue ambiguous.…”
Section: Introductionmentioning
confidence: 99%